Effect of Unilateral Shoulder Disorder on the Stance Phase of Human Gait - Martin Missmann; Gerald Aron; Thomas Stöggl; Michael Pirchl; Vincent Grote; Michael J. Fischer (The Scientific World Journal)
Background. Gait analysis systems serve as important tools for assessing disturbed gait patterns. Amongst other factors, functional limitations of the shoulder joint may relate to such disturbances. Patient-reported outcome measures, assessment of pain, and active range of motion are commonly used to describe shoulder impairment. Purpose. The aim of this cohort study was to evaluate the impact of unilateral limitations of shoulder mobility and pain on gait patterns and to detect correlations between pain, shoulder mobility, and particular phases of human gait using a Zebris gait analysis system. Methods. 20 subjects with unilaterally restricted mobility and pain of the affected shoulder and a control group of 10 healthy subjects underwent a gait analysis. Various gait parameters, the DASH score, pain at rest and movement of the affected shoulder, and the active range of motion (aROM) for shoulder flexion and abduction were recorded. Results. We determined significant differences of the duration of the loading response (p = 0.021), midstance (p = 0.033), and the terminal stance phase (p = 0.019) between the shoulder group and the control group, with a shorter loading response phase and a longer terminal stance phase of the affected side in the shoulder group. In the shoulder group, we found significant correlations between the DASH and the duration of the midstance phase (p = 0.023) and the terminal stance phase (p = 0.038). In addition, there was a significant correlation between shoulder flexion and the duration of the midstance phase (p = 0.047).